A Critical Study of French Versification and Poetic Genres - Hadi Dolatabadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Criticism of books and authors’ works is aimed at creating dynamics in the academic, literary, and academic circles and can, if neutral and constructive, lead to progress, dialogue between experts, and improved efficiency. In the field of academic books, this can also lead to deficiencies and complete writing of works. The Book of French Poetry by the Honorable Shahnaz Shahin and Mahvash Ghavimi, published by the University Academic Press, has been published in 2000 and has been reviewed and edited in 2004. Designed with an academic audience to teach undergraduate and postgraduate courses in French literature, the book has some drawbacks, despite its clear writing. The purpose of this paper is to examine the writing and presentation of this book’s material and to address some of the shortcomings, mainly in the form of the arrangement of contents within the book’s chapters, the citation system, and the examples presented from a formal point of view. The content commentary refers to the overemphasis on French poetic form and the lack of a comprehensive introduction of French poets and their influential works.